Foreign languages for the use of printers and translators : - Ostermann, George F. Von (Washington D. C., 1934)
This manual relating to foreign languages is purposely condensed for ready reference and is intended merely as a guide, not a textbook.Only elementary rules and examples are give, and no effort is made to deal exhaustively with any one subject.